Ancient and Near Eastern Glass. The Toledo Museum of Art founded by Edward Drummond Libbey - Riefstahl, Rudolf M. (1966)
espec. fig. 3, p. 2: Mold-pressed amulet of Astarte. Translucent blue glass. Eastern Mediterranean, possibly Syria, ca. 1500 B.C.